SOCIO-TECHNICAL INNOVATIONS IN PUBLIC HEALTH: A REVIEW OF DIGITAL INTERVENTIONS ENHANCING HEALTH OUTCOMES IN VULNERABLE COMMUNITIES - Ayumi Nonumora; Aneta Rasińska; Paulina Bala; Justyna Matusik; Piotr Rzyczniok; Mateusz Kopczyński; Justyna Jachimczak (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Objective: Digital health interventions are increasingly recognized as vital tools for improving public health outcomes, especially in vulnerable communities facing social and economic challenges. This review examines socio-technical innovations that leverage digital technologies to enhance health equity and access to care. Review Methods: A comprehensive literature review was conducted using peer-reviewed sources published between 2015 and 2023 from databases including PubMed, Scopus, and Web of Science. Studies were selected based on their focus on interdisciplinary approaches combining technology, healthcare, and public health to address disparities in vulnerable populations. Both qualitative and quantitative findings were synthesized through thematic analysis to identify key patterns and challenges. State of Knowledge: Findings highlight effective digital interventions such as telemedicine, mobile health applications, remote monitoring, and community-based digital platforms that improve access and engagement. Persistent barriers include the digital divide, privacy concerns, socioeconomic factors, and technology acceptance. Interventions employing participatory design and culturally tailored strategies tend to yield more sustainable outcomes. Conclusion: Socio-technical digital health innovations hold promise for advancing health equity by integrating technological solutions with social and healthcare needs. To optimize impact, future efforts should emphasize equitable design, policy support, and continuous evaluation. This review underlines the importance of interdisciplinary collaboration to build resilient and inclusive public health systems through digital means.